Medical abortion at 13 or more weeks gestation provided through telemedicine: A retrospective review of services - Nathalie Kapp; Kathryn Andersen; Risa Griffin; Amalia Puri Handayani; Marlies Schellekens; Rebecca Gomperts (Elsevier, 2021)
Objectives: To evaluate medical abortion effectiveness and safety in women at 13 or more weeks gestation provided care through Women on Web's telemedicine service. Study Design: We conducted a retrospective case study of abortions at 13 or more weeks gestation provided by Women on Web between 2016 and 2019. Women received mifepristone and misoprostol or misoprostol alone for abortion. We extracted demographic characteristics and outcome data for cases with pregnancy continuation outcomes. Results: We identified 144 women who used medical abortion at 13 or more weeks; 131 (91%) provided abortion outcome data. Almost all, 118 (90%) received mifepristone and misoprostol. The population had an average age of 26 ± 5.8 years, 102 (78%) reported a gestational age of 13 to 15 weeks, 114 (87%) had experienced prior pregnancy, and represented all world regions. Overall, 13 (10%) women reported a continuing pregnancy, with 5 (5%) among women 13 to 15 weeks and 8 (28%) among those ≥16 weeks (p = 0.001); 38 (29%) reported adverse events (heavy bleeding, fever), 53 (43%) sought additional care from a health provider, and 18% of all cases received treatment with D&C/aspiration. Conclusions: Efficacy of self-administered medical abortion decreases as gestational age increases, risking continuation of pregnancy. Provision through telemedicine at 13 to 15 weeks appears safe and effective. Implications: Limited data suggest that medical abortion through telemedicine services may be a safe option through 15 weeks gestation in settings where there is ready access to the formal health system. More research with adequate sample sizes and high rates of follow-up is needed to inform on the safety of telemedicine for pregnancies 13 weeks and greater.